The investigation of chemical coagulation and electrocoagulation processes for tannery wastewater treatment using response surface methodology - Erkan, Hanife Sari; Guvenc, Senem Yazici; Varank, Gamze; Engin, Guleda Onkal (DESALINATION PUBL, 2018)
This study deals with the comparison of chemical coagulation (CC) (using aluminum sulphate and iron chloride as coagulants) and electrocoagulation (EC) (using aluminium and iron electrodes) processes for TOC and total chromium removal from tannery industry wastewater. The parameters, namely, the coagulant dosage (for CC), current density (for EC), reaction time, and initial pH (for both processes) were optimized employing central composite design (CCD) of response surface methodology (RSM). Experimental data was analyzed by means of the analysis of variance (ANOVA) identifying the mechanism of interaction between the process variables and the dependent variables. High TOC removal efficiencies were obtained in the CC process (60.8% and 75.6% using aluminum sulphate and iron chloride, respectively) and the EC process (75.0% and 84.6% using aluminum and iron electrodes, respectively). No significant difference between CC and EC processes was found for the removal of total chromium in the optimum operation conditions (total chromium removal was over 98% for each process configuration). Even though an appreciable improvement in TOC and total chromium removal efficiencies were obtained in both processes, the CC process using iron chloride was found to be more effective to remove total chromium considering the operational costs.
Keywords: Tannery wastewater; Chemical coagulation; Electrocoagulation; Response surface methodology; Optimization; ELECTROCHEMICAL TREATMENT; ALUMINUM ELECTRODES; TRIVALENT CHROMIUM; INDUSTRIAL-WASTE; REVERSE-OSMOSIS; IRON ELECTRODES; REMOVAL; WASTEWATERS; EFFLUENT; Engineering; Water Resources